Effects of different light intensities, fertilizer levels and shading periods on three shade-tolerant tree species under controlled environment - Hamad, Sherzad Omar (2016)
With the increasing demand of heavy hardwood timbers in the world market annually, many of the shade-tolerant tree species such as Neobalanocarpus heimii, Shorea materialis and Intsia palembanica in Malaysia have faced serious extinction. The overall objective of this study was to improve growth and physiological properties of the aforementioned species through better understanding of their ecophysiology and growth requirements. For this purpose, two experiments were conducted in the shade house and open area, where the first research was done to investigate the effect of different light intensities, and fertilizer levels on the survival rate, growth performance and physiological traits of the three species; the second research was performed to identify the effect of four shading periods on the survival rate, growth, biomass, leaf morphology and leaf physiology of the selected species. The first experiment results after six months of the study indicated that the survival percentage of S. materialis and I. palembanica was 100% under all treatments. However, the survival percentage of N. heimii was significantly affected only by the light intenities, where its highest survival rate was 100% under 30% and 50% RLI, while the lowest survival rate was 74.07% at 100% RLI. All growth parameters and most physiological traits of these three species were significantly higher at both shade conditions (30% and 50% RLI) than full sunlight. Application of various fertilizer levels had a different effect on the growth and physiological properties of the species. Nevertheless, most parameters were enhanced by the application 1 and/or 2g NPK monthly. The results of the second experiment after twelve months showed that the survival rate of S. materialis and I. palembanica was 100% under all shade periods. Conversely, the survival rate of N. heimii was significantly reduced to 66.66% in zero shade periods while it was 100% in other shade periods. Seedlings of the three species grown under the shade for six, nine, and twelve months were significantly recorded higher height, diameter, and leaf numbers compared to those that have not been under shade. Stem mass, leaves mass, root mass and total plant mass were also affected by different shade periods. The highest value of these parameters were found in nine months under shade for N. heimii, and S. materialis, and six months under shade for I. palembanica while the lowest value of their biomass allocation were observed in zero month under shade. These three species displayed typical responses to direct sunlight after the canopy openings such as increases in RMR, R:SR and stomatal density and reduction in leaf area, SLA, LAR, and chlorophyll content except SLA, and LAR of I. palembanica at the first canopy opening. Photosynthetic rate and stomatal conductance of the three species indicated that their photosynthesis apparatus can acclimate to direct sunlight, especially after the second and third canopy opening. In conclusion, growth and physiological properties of the three species were improved by application of 1g and 2g fertilizer under 30% and 50% RLI. In addition, the species could acclimatise to direct sunlight after they had been grown under shade (30% - 50% RLI) for six to nine months additionally (to their shade periods prior the study) due to their ability to adjust their morphological and physiological behaviors in accordance with changing light condition.